2011
DOI: 10.4238/vol10-3gmr1153
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic and bioinformatic analysis of outer membrane proteins of the protobacterium Bartonella henselae (Bartonellaceae)

et al.

Abstract: ABSTRACT. Bartonella henselae, an infectious agent causing catscratch disease and vasculoproliferative disorders in humans, is a fastidious facultative intracellular pathogen. The outer membrane proteins of B. henselae are key molecules that play a primary role in host-cell interactions. We isolated B. henselae outer membrane proteins, using the ionic detergent N-lauroyl sarcosine sodium salt and sodium carbonate, purification by two-dimensional (2-D) gel electrophoresis, and protein identification using mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…We failed to detect HbpB in B. henselae using the western blot method. This result is in good agreement with those of proteomic analysis of outer membrane fractions of B. henselae and B. quintana [51], [52], [53], [54], [55], [56], which showed that HbpB was not detectable using this method. Since HbpA is the most abundant Hbp in B. henselae [52], [51], we checked its level in B. henselae pNS2Trc and B. henselae pNS2Trc ::hbpA AS using mouse antibody directed against HbpB.…”
Section: Resultssupporting
confidence: 90%
“…We failed to detect HbpB in B. henselae using the western blot method. This result is in good agreement with those of proteomic analysis of outer membrane fractions of B. henselae and B. quintana [51], [52], [53], [54], [55], [56], which showed that HbpB was not detectable using this method. Since HbpA is the most abundant Hbp in B. henselae [52], [51], we checked its level in B. henselae pNS2Trc and B. henselae pNS2Trc ::hbpA AS using mouse antibody directed against HbpB.…”
Section: Resultssupporting
confidence: 90%
“…The proteomes of whole cells and subcellular fractions of B. quintana and B. henselae have been analyzed by two-dimensional gel electrophoresis and MALDI-TOF-MS of the protein spots. For example, two studies identified 44 [164] and 53 [165] proteins associated with the B. henselae outer membrane fractions. A third study analyzed the B. quintana membrane subproteome and found 60 proteins [166].…”
Section: Diagnostics and Identificationmentioning
confidence: 99%
“…Second, our expressed proteome encompassed all proteins identified in three previous B. henselae proteomics studies (Rhomberg et al 2004;Eberhardt et al 2009;Li et al 2011), while adding many more low-abundance proteins (Supplemental Fig. S6A-C).…”
Section: Evidence For Having Reached An Expressed Proteome Endpointmentioning
confidence: 99%